Leprosy : past and present - Roberts, Charlotte A. (Bioarchaeological interpretations of the human past., 2020)
"Through an unprecedented multidisciplinary and global approach, this book documents the dramatic 7,000-year history of leprosy using bioarchaeological, clinical, and historical information from a wide variety of contexts, dispelling many longstanding myths about the disease"--